Autonomy of educational centers (intervention of the Inspection of Education) - Fernando Tébar Cuesta (ADIDE Federación, 2018)
The autonomy of the centers is presented as an instrument to achieve educational purposes. After a tour of the main points in the reference normative evolution, we come to the real options of exercising it in an educational center: autonomy to make decisions in the pedagogical field; autonomy to organize themselves according to their own criteria and autonomy to manage their personal and material resources. The core of the work revolves around the analysis of the elements that define autonomy, such as: the project itself, a professional direction, the fundamental role of the teaching staff and the necessary evaluation. In the last part a proposal is drawn up for the intervention from the educational inspection on the basis of the autonomy of the centers.